LED phototherapy in full-thickness burns induced by CO2 laser in rats skin - da Silva Melo, Milene; Alves, Leandro Procópio; Fernandes, Adriana Barrinha; Carvalho, Henrique Cunha; de Lima, Carlos José; Munin, Egberto; Gomes, Mônica Fernandes [UNESP]; Salgado, Miguel Angel Castillo [UNESP]; Zângaro, Renato Amaro (Springer Nature, 2018)
Many studies have been conducted on the treatment of burns because they are important in morbidity and mortality. These studies are mainly focused on improving care and quality of life of patients. The aim of this study was evaluate the LED phototherapy effects in rats skin full-thickness burns induced by CO2 laser. The animals were divided in NT group that did not received any treatment and LED group that received LED irradiation at 685 nm, 220 mW, and 4.5 J/cm2 during 40 s by burned area. Biopsies were obtained after 7, 14, and 21 days of treatment and submitted to histological and immunohistochemical analysis. The LED phototherapy shows anti-inflammatory effects, improves angiogenesis, and stimulates the migration and proliferation of fibroblasts. The T CD8+ lymphocytes were more common in burned areas compared to T CD4+ lymphocytes since statistically significant differences were observed in the LED group compared to the NT group after 7 days of treatment. These results showed that LED phototherapy performs positive influence in full-thickness burns repair from the healing process modulated by cellular immune response. The obtained results allowed inferring that burns exhibit a characteristic cell immune response and this cannot be extrapolated to other wounds such as incision and wounds induced by punch, among others.
Keywords: CO2 laser; Full-thickness burns; Histology; Immunohistochemistry; LED phototherapy; Lymphocytes T CD4+ and T CD8+; Wound healing